The Teacher Challenges in Planning English Reading - Maulida Maulida; Asmaul Husna; Tara Arini; Syahwan Hamdany; Santi Sari Devi; Khairun Nisa Simanjuntak (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
Planning effective English reading lessons is a complex task for teachers because of challenges such as variations in student ability levels, limited resources, and time constraints. This research aims to identify the main challenges teachers face in planning reading lessons, including improving students' reading comprehension, adjusting the level of support to students' abilities, and implementing reading strategies. The research method used is qualitative, with data collection through semi-structured interviews with teachers from various levels of education. Data were analyzed using thematic analysis to identify main patterns and themes. The research results show that teachers face challenges in managing the diversity of students' reading abilities, selecting reading materials that are interesting and culturally relevant, and integrating technology into learning. Additionally, appropriate assessments for English Language Learners (ELL) students and the need to provide emotional support to students are also challenges. Limited professional training and resources contribute to this situation. This research also concludes that successful learning to read English requires a multifaceted approach that includes learning adjustments, teacher training, collaboration, and access to a variety of reading materials. By providing adequate support for teachers, these obstacles can be overcome, so that reading learning becomes more effective and inclusive.